The Influence of Workload, Job Stress, and Work Environment on Turnover Intention of Inpatient Nurses at Wiyung Sejahtera Hospital - Syech Noval Kurnia Ramadhan; Bowo Santoso (Management Science Research Journal, 2026)
This study analyzes the influence of workload, job stress, and the work environment on nurses turnover intentions at Wiyung Sejahtera Hospital. The quantitative method used was Partial Least Squares–Structural Equation Modeling (PLS-SEM), involving 99 inpatient nurses using a Likert-scale questionnaire. The results show that workload and job stress have a significant positive effect on turnover intentions, meaning that the higher the workload and stress, the greater the nurse's intention to leave. Conversely, the work environment has a negative effect, meaning a positive environment can reduce turnover intentions. These findings emphasize the importance of managing workload, reducing job stress, and creating a conducive work environment to improve healthcare worker retention and the quality of hospital services. The study also discusses variable indicators and instrument validity and reliability, and provides strategic recommendations for human resource management in healthcare institutions.